Seroprevalence of hepatitis E virus infection among dogs in several developed cities in the Guangdong province of China. Issue 8 (2nd February 2016) - Wang, Lifang; Zheng, Yun; Fu, Cheng; Huang, San; Hong, Malin; Yan, Zhongshan; Jia, Kun; Zhou, Pei; Li, Shoujun
Abstract : Hepatitis E virus (HEV), as a zoonotic disease virus, was seldom studied in dogs especially in stray dogs. As previously reported, dog might be an accidental host of HEV for human beings and some risk factors might play an important role in HEV transmission. Thus, we designed this study to evaluate the seroprevalence of HEV infection among dogs in several cities in Guangdong province of China. This surveillance may help us understand risk factors including location, gender, live type, and diet habit for HEV transmission. The overall seroprevalence of anti‐HEV antibodies in dogs was 19.00%. Positive rate of anti‐HEV antibodies in other food groups (21.13%) was higher than that in dog food groups (9.77%) ( P  < 0.05), which suggested that diet habit might be a vital element of infecting HEV for dogs and play an important role in living environment. However, the analysis indicated that no strong relationship was observed among different cities, gender groups, and live type. Our study demonstrated that HEV is prevalent in dogs in the Guangdong province of China. As diet habit might become a vital element of infecting HEV for dogs and play an important role in living environment, similar studies of dogs should be conducted in the future. J. Med. Virol. 88:1404–1407, 2016 . © 2016 Wiley Periodicals, Inc.